Functionalization of filled radioactive multi-walled carbon nanocapsules by arylation reaction for in vivo delivery of radio-therapy. Issue 1 (29th November 2021) - Gajewska, Agnieszka; Wang, Julie T.-W.; Klippstein, Rebecca; Martincic, Markus; Pach, Elzbieta; Feldman, Robert; Saccavini, Jean-Claude; Tobias, Gerard; Ballesteros, Belén; Al-Jamal, Khuloud T.; Da Ros, Tatiana
Abstract : In vivo studies of 153 SmCl3 @MWCNTs, functionalized with an optimized procedure, show their high accumulation mainly in lung, liver and spleen, prompting the suitability to passively target various tumor types in future efficacy studies in animals. Abstract : Functionalized multi-walled carbon nanotubes (MWCNTs) containing radioactive salts are proposed as a potential system for radioactivity delivery. MWCNTs are loaded with isotopically enriched 152-samarium chloride ( 152 SmCl3 ), the ends of the MWCNTs are sealed by high temperature treatment, and the encapsulated 152 Sm is neutron activated to radioactive 153 Sm. The external walls of the radioactive nanocapsules are functionalized through arylation reaction, to introduce hydrophilic chains and increase the water dispersibility of CNTs. The organ biodistribution profiles of the nanocapsules up to 24 h are assessed in naïve mice and different tumor models in vivo . By quantitative γ-counting, 153 SmCl3 @MWCNTs-NH2 exhibite high accumulation in organs without leakage of the internal radioactive material to the bloodstream. In the treated mice, highest uptake is detected in the lung followed by the liver and spleen. Presence of tumors in brain or lung does not increase percentage accumulation of 153 SmCl3 @MWCNTs-NH2 in the respective organs, suggesting the absence of the enhanced permeation and retention effect. This study presents a chemical functionalization protocol that is rapid (∼one hour) and can be applied to filled radioactive multi-walled carbon nanocapsules to improve their water dispersibility for systemic administration for their use in targeted radiotherapy.